2005
DOI: 10.1038/sj.mp.4001763
|View full text |Cite
|
Sign up to set email alerts
|

Procholinergic and memory enhancing properties of the selective norepinephrine uptake inhibitor atomoxetine

Abstract: Atomoxetine has been approved by the FDA as the first new drug in 30 years for the treatment of attention deficit/hyperactivity disorder (ADHD). As a selective norepinephrine uptake inhibitor and a nonstimulant, atomoxetine has a different mechanism of action from the stimulant drugs used up to now for the treatment of ADHD. Since brain acetylcholine (ACh) has been associated with memory, attention and motivation, processes dysregulated in ADHD, we investigated the effects of atomoxetine on cholinergic neurotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
88
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 32 publications
4
88
0
Order By: Relevance
“…However, evidence of a primary role for dopamine in mediating the nicotine cue is lacking, as selective dopamine antagonists generally fail to alter nicotine discrimination or attenuate nicotine discrimination only at doses that suppress response rates (Brioni et al, 1994;Corrigall and Coen, 1994;Le Foll et al, 2005). Since methylphenidate also elevates extracellular levels of acetylcholine in addition to dopamine (Tzavara et al, 2006), it may be that methylphenidate enhances nicotine's discriminative stimulus effects via a primarily nondopaminergic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence of a primary role for dopamine in mediating the nicotine cue is lacking, as selective dopamine antagonists generally fail to alter nicotine discrimination or attenuate nicotine discrimination only at doses that suppress response rates (Brioni et al, 1994;Corrigall and Coen, 1994;Le Foll et al, 2005). Since methylphenidate also elevates extracellular levels of acetylcholine in addition to dopamine (Tzavara et al, 2006), it may be that methylphenidate enhances nicotine's discriminative stimulus effects via a primarily nondopaminergic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms by which atomoxetine antagonized these nicotine-related behaviors will require further investigation. However, research suggests a possible role of cortical norepinephrine, dopamine, and/or acetylcholine efflux (Tzavara et al, 2006). One suggestion for the procholinergic property is that converging dopamine and norepinephrine neurons modulate cortical acetylcholine release at the nucleus basalis (Tzavara et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Forebrain cholinergic systems are essential for cognitive processes, such as learning, memory and attention, 3 and procholinergic drugs are procognitive in the clinic. 3,4 Importantly, obesity appears to be comorbid with disease states characterized by cognitive impairment, for example, attentiondeficit hyperactivity disorder (ADHD). 5 It is hypothesized that an integral prefrontal cortical function, especially in the right hemisphere, might be critical for appetite and eating control, as well as for better long-term adherence to therapeutic interventions.…”
mentioning
confidence: 99%
“…2,6 We have recently shown that clinically established ADHD drugs increase acetylcholine (ACh) efflux preferentially in the medial PFC of rats, a neurochemical effect that may be related to their therapeutic action. 4 We sought to investigate the effects of the efficacious antiobesity drugs, 7 sibutramine (a monoamine reuptake inhibitor) and rimonabant (a cannabinoid CB 1 receptor antagonist), on ACh efflux in the PFC and in a subcortical brain region implicated in food reward/reinforcement processes, the nucleus accumbens (NAC), of freely moving rats by in vivo microdialysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation